Enhanced therapeutic efficacy of doxorubicin against multidrug-resistant breast cancer with reduced cardiotoxicity - Tianyu Zhang; Nuannuan Li; Ru Wang; Yiying Sun; Xiaoyan He; Xiaoyan Lu; Liuxiang Chu; Kaoxiang Sun (Taylor & Francis Group, 2023)
AbstractDoxorubicin (DOX), a commonly used anti-cancer drug, is limited by its cardiotoxicity and multidrug resistance (MDR) of tumor cells. Epigallocatechin gallate (EGCG), a natural antioxidant component, can effectively reduce the cardiotoxicity of DOX. Meanwhile, EGCG can inhibit the expression of P-glycoprotein (P-gp) and reverse the MDR of tumor cells. In this study, DOX is connected with low molecular weight polyethyleneimine (PEI) via hydrazone bond to get the pH-sensitive PEI-DOX, which is then combined with EGCG to prevent the cardiotoxicity of DOX and reverse the MDR of cancer cells. In addition, folic acid (FA) modified polyethylene glycol (PEG) (PEG-FA) is added to get the targeted system PEI-DOX/EGCG/FA. The MDR reversal and targeting ability of PEI-DOX/EGCG/FA is performed by cytotoxicity and in vivo anti-tumor activity on multidrug resistant MCF-7 cells (MCF-7/ADR). Additionally, we investigate the anti-drug resistant mechanism by Western Blot. The ability of EGCG to reduce DOX cardiotoxicity is confirmed by cardiotoxicity assay. In conclusion, PEI-DOX/EGCG/FA can inhibit the expression of P-gp and reverse the MDR in tumor cells. It also shows the ability of remove oxygen free radicals effectively to prevent the cardiotoxicity of DOX.